The Analysis of Added Value and Business Development Strategies for the Semboro Orange Extract Agroindustry Using the High Pulsed Electric Field (HPEF) Pasteurization System - Hariono, Budi; Kurnianto, Mokhamad Fatoni; Brilliantina, Aulia (P3M Politeknik Negeri Jember, 2024)
Semboro Siamese oranges have a higher selling value However, the selling value of the Siamese oranges is still relatively low, thus some efforts need to be made to increase the added value of the Siamese oranges. One way that can be done is by producing Siamese orange extract using the High Pulsed Electric Field (HPEF) technology. The aim of this research is to determine the added value and business development strategies of the HPEF Siamese orange extract. The analysis methods used were Hayami and SWOT. The research results show that there is a linearity between the two methods which indicates a positive value with a ratio of value and added value that is classified as high category, and there are development strategies that can be implemented by expanding marketing areas and improving product quality and safety by applying the existing technology.